Defense Advanced Research Projects Agency: Comment on 'Engineering biology and the grand challenges: Do we need a new R&D&I model?'. Issue 2 (31st March 2021) - Klabukov, Ilya; Krasilnikova, Olga
Abstract: This comment paper refers to the article published by Gauvreau et al. in Engineering Biology in 2018. Gauvreau et al. discussed various civilian models in the private and public sectors that could boost R&D plus Innovation (R&D&I) progress in the environmental sphere. The authors concluded that there is no tried‐and‐tested R&D&I model for engineering biology that is suited to help solve the problems of many grand and interacting challenges, and further, that the required model will not work without the private sector, so governments must collaborate to develop such a model. However, the authors have not mentioned one of the most famous classic Research & Development (R&D) models used in the creation of disruptive technologies—a unique model of the Defense Advanced Research Projects Agency (DARPA) of the US Department of Defense. The present commentary poses questions about the models currently used in innovative research, known as DARPA‐like R&D agencies, and the innovative ecosystems around them.